Study of water management problems in Muda Irrigation Scheme / Aznan Ismail - Ismail, Aznan (1985)
The content of this report focuses on the major water management problems faced in supplying irrigation water for the double cropping of padi in the Muda Irrigation Scheme. , Irrigation water for the scheme comes from three sources, i.e from the storage reservoirs, the uncontrolled flow and the direct rainfall. Most of the problems are at the distribution, and at the farm level and minor problems also exist within the control and conveyance system. Hater management is an integrated process, ranging from supply, drainage operation and maintenance to secure maximum crop yield with economic use of water. Thus, it covers very wide scope and aspects.